Strategi Komunikasi Humas Pemandu dan Pemasaran Dalam Menyampaikan Narasi Sejarah Kepada Pengunjung Di Monumen Jogja Kembali - Shalita Ummi Gaisani; Alfian Muhazir; Olla Agustina (CV. ITTC INDONESIA, 2026)
As a medium for historical education, museums require effective communication strategies to ensure that historical narratives are understood by visitors with diverse backgrounds. This study aims to analyze the communication strategies employed by public relations staff, tour guides, and marketing teams in conveying historical narratives to visitors at the Monumen Jogja Kembali. The research employs a descriptive method with a qualitative approach. Data were collected through in-depth interviews, observation, and documentation, and subsequently analyzed using the Miles and Huberman interactive model. The findings indicate that communication strategies are implemented by tailoring language and narratives to visitor characteristics, utilizing a combination of verbal communication and educational media, and strengthening communication through digital channels and inter-departmental coordination. However, challenges remain, specifically regarding varying levels of visitor comprehension and limitations in tour guide services. The study concludes that adaptive and integrated communication strategies can enhance the effectiveness of conveying historical narratives and reinforce the museum’s educational role in preserving historical values.